A randomized Phase II study of veliparib with temozolomide or carboplatin/paclitaxel versus placebo with carboplatin/paclitaxel in BRCA1/2 metastatic breast cancer: design and rationale. (February 2017) - Isakoff, Steven J; Puhalla, Shannon; Domchek, Susan M; Friedlander, Michael; Kaufman, Bella; Robson, Mark; Telli, Melinda L; Diéras, Véronique; Han, Hyo Sook; Garber, Judy E; Johnson, Eric F; Maag, David; et al.
Veliparib is an orally administered poly(ADP-ribose) polymerase inhibitor that is being studied in Phase I–III clinical trials, including Phase III studies in non-small-cell lung cancer, ovarian cancer and breast cancer. Tumor cells with deleterious BRCA1 or BRCA2 mutations are deficient in homologous recombination DNA repair and are intrinsically sensitive to platinum therapy and poly(ADP-ribose) polymerase inhibitors. We describe herein the design and rationale of a Phase II trial investigating whether the addition of veliparib to temozolomide or carboplatin/paclitaxel provides clinical benefit over carboplatin/paclitaxel with placebo in patients with locally recurrent or metastatic breast cancer harboring a deleterious BRCA1 or BRCA2 germline mutation (Trial registration: EudraCT 2011-002913-12, NCT01506609).